FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PADA SCOOT FAST CRUISES DI BALI - Ardane, Nengah; Sofia Wijaya, Ni Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
Mode of water transport is very important in the tourism industry as a support in providing the best service for tourists. Transportation is the cause and the effect of the growth of tourist in Bali. Scoot Fast Cruises is transport services to Lembongan, Lombok and Senggigi. Based on Trip Advisor rating in the quality of service that is provided by Scoot Fast Cruises still very poor (158). This study aims to determine the factors that affect the service quality at Scoot Fast Cruises in Bali. Sampling technique used in this study using purposive sampling of respondents are crossing service users Scoot Fast Cruises in Bali with a total sample of 100 respondents. The data collection techniques using a questionnaire that was tested using the test validity and reliability. Analysis of the data used in this study is factor analysis using SPSS 17.0. The results of the factor analysis there are three factors that affect the service quality at Scoot Fast Cruises in Bali that is a factor completeness of facilities and services to get service with a value of eigen value 7.390, factor accuracy of services to the value of eigen value of 1.397 and the convenience factor rating with eigen values ??value amounting to 1.307. Factors completeness and ease of getting care facilities is a contributing factor dominant in influencing quality of tourist services at Scoot Fast Cruises in Bali. For further research that will lift the title of the research about the factors that affect the quality of service on a fast boat to take a shuttle to the hotel indicators and increasing the number of respondents and indicators. As for the company Scoot Cruises to take into account the convenience of tourists.
Keywords: Service Quality, Fast Cruises